Dinamika Sosioekonomi Pada Ilmu Ekonomi Islam Klasik - Rikmat Ismatullah (Universitas Alma Ata, 2009)
M. Umer Chapra discusses various concepts that related to the Islamic economic system and compare with the conventional economic system, directions and challenges facing the Islamic economy in the future as well as, as the central theme of his book, he picked up the concept of Ibn Khaldun's economic development. Interestingly, he managed to formulate the concept into a cycle that is easy to understand.He not only succeeded in formulating the concept of Ibn Khaldun into the cycle of increase progress and decrease cycles, but also he was able to further define the relationship between one component of development linkages with other components. Ibn Khaldun explains the important for the development of Sharia (S), the development community (W), law enforcement and other Development (j & g), as well as the role of Government (G). Umer Chapra formulate these components in the cycle, the cycle advances toward him: SNW-j & g-GS and other cycle: j & g-WNSG-j & g. In this article, he discusses about some of the thinking of classical Islamic scholars who provide the base foundation in the concept of Islamic economics in particular Ibn Khaldun in his several works such as the Muqaddimah, which tried to determine factors affecting quality by analyzing factors such as the role of interconnected moral factors, psychological, political, economic, social, demographic, and historical phenomena of the rise and fall of dynasties and civilizations.Keywords: Capra, Systems, Economics, Islam.